ANALISIS USER EXPERIENCE PENGGUNA APLIKASI OBENKYO MENGGUNAKAN METODE HEURISTIC EVALUATION - Tandriady, Kevin; Zaman, Baizul; Bahri, Syamsul (JTRISTE, 2024)
Nowadays the development of anime coupled with the rapid advancement of technology makes anyone can enjoy this entertainment, other Japanese popular culture products also include manga (Japanese comics), dorama (Japanese TV dramas), and Japanese popular music such as J-pop and J-rock also affect the interest in learning Japanese language and culture for young people. This research uses the Heuristic Evaluation method which is a method used to find problems in the interface design of an application and look for the positive side of the application. The data source of this research uses primary data, namely a questionnaire wheare the data collected is 15 respondents in the Makassar Jejepangan community and secondary data, namely literature studies or references from other journals. The results showed that of the 10 aspects of the Heuristic Evaluation method, there are 3 aspects that have Minor Usability Problems or there are problems that interfere with user comfort with a severity rating value of 2, or improvements are needed with a low priority level. And the other 7 aspects are worth 1 or Cosmetic Problem meaning only problems that do not affect users, and there are no aspects with a value of 0 or Don't Agree which means there are no problems at all. User Experience of Obenkyo users in the Makassar jejepangan community shows that there are more male Obenkyo users than female and some users also feel satisfied using this application.